DNA Nanostructures in the Fight Against Infectious Diseases. Issue 3 (6th January 2021) - Smith, David M.; Keller, Adrian
Abstract : Throughout history, humanity has been threatened by countless epidemic and pandemic outbreaks of infectious diseases, from the Justinianic Plague to the Spanish flu to COVID‐19. While numerous antimicrobial and antiviral drugs have been developed over the last 200 years to face these threats, the globalized and highly connected world of the 21st century demands for an ever‐increasing efficiency in the detection and treatment of infectious diseases. Consequently, the rapidly evolving field of nanomedicine has taken up the challenge and developed a plethora of strategies to fight infectious diseases with the help of various nanomaterials such as noble metal nanoparticles, liposomes, nanogels, and virus capsids. DNA nanotechnology represents a comparatively recent addition to the nanomedicine arsenal, which, over the past decade, has made great progress in the area of cancer diagnostics and therapy. However, the past few years have seen also an increasing number of DNA nanotechnology‐related studies that particularly focus on the detection and inhibition of microbial and viral pathogens. Herein, a brief overview of this rather young research field is provided, successful concepts as well as potential challenges are identified, and promising directions for future research are highlighted. Abstract : Infections arising from pathogenic organisms such as viruses and bacteria represent a dire threat to modern society due to their impact on human health as well as the potential for economic and societal disruption in the case of global pandemics. Approaches to detect and treat infectious diseases based on DNA nanostructures offer many promising, although still widely unexplored, possibilities.